Islamic Republic of Mauritania : Sixth Review Under the Three Year Extended Credit Facility Arrangement and Request of Nonobservance of Performance Criterion-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses the Islamic Republic of Mauritania's Sixth Review under the Three-Year Extended Credit Facility Arrangement and Request of Nonobservance of Performance Criterion. Mauritania's current account deficit has been significantly widened due to higher infrastructure and mining-related imports. Planned projects are concentrated in agriculture, energy, and infrastructure-all three sectors with large investment needs and in line with Poverty Reduction Strategy Paper priorities. Nonrenewable resources are playing an important role in the economy, but the fiscal policy formulation does not incorporate the challenges associated with resource revenue exhaustibility and volatility and, therefore, does not prevent pro-cyclical fiscal policy.